Adenosine kinase attenuates cardiomyocyte microtubule stabilization and protects against pressure overload-induced hypertrophy and LV dysfunction. (May 2019) - Fassett, John; Xu, Xin; Kwak, Dongmin; Zhu, Guangshuo; Fassett, Erin K.; Zhang, Ping; Wang, Huan; Mayer, Bernd; Bache, Robert J.; Chen, Yingjie
Abstract: Adenosine exerts numerous protective actions in the heart, including attenuation of cardiac hypertrophy. Adenosine kinase (ADK) converts adenosine to adenosine monophosphate (AMP) and is the major route of myocardial adenosine metabolism, however, the impact of ADK activity on cardiac structure and function is unknown. To examine the role of ADK in cardiac homeostasis and adaptation to stress, conditional cardiomyocyte specific ADK knockout mice (cADK −/− ) were produced using the MerCreMer-lox-P system. Within 4 weeks of ADK disruption, cADK −/− mice developed spontaneous hypertrophy and increased β-Myosin Heavy Chain expression without observable LV dysfunction. In response to 6 weeks moderate left ventricular pressure overload (transverse aortic constriction;TAC), wild type mice (WT) exhibited ~60% increase in ventricular ADK expression and developed LV hypertrophy with preserved LV function. In contrast, cADK −/− mice exhibited significantly greater LV hypertrophy and cardiac stress marker expression (atrial natrurietic peptide and β-Myosin Heavy Chain), LV dilation, reduced LV ejection fraction and increased pulmonary congestion. ADK disruption did not decrease protein methylation, inhibit AMPK, or worsen fibrosis, but was associated with persistently elevated mTORC1 and p44/42 ERK MAP kinase signaling and a striking increase in microtubule (MT) stabilization/detyrosination. In neonatal cardiomyocytes exposed to hypertrophic stress, 2-chloroadenosine (CADO) or adenosine treatment suppressed MT detyrosination, which was reversed by ADK inhibition with iodotubercidin or ABT-702. Conversely, adenoviral over-expression of ADK augmented CADO destabilization of MTs and potentiated CADO attenuation of cardiomyocyte hypertrophy. Together, these findings indicate a novel adenosine receptor-independent role for ADK-mediated adenosine metabolism in cardiomyocyte microtubule dynamics and protection against maladaptive hypertrophy.